Improving Hilbert–Huang transform for energy-correlation fluctuation in hydraulic engineering. (1st December 2018) - Lu, Shibao; Zhang, Xiaoling; Shang, Yizi; Li, Wei; Skitmore, Martin; Jiang, Shuli; Xue, Yangang
Abstract: Intense vibrations in hydraulic turbine generator unit draft tubes lead to a run-out of the unit shafting and threaten its safe and stable operation. Correct maintenance is therefore important for the safe operation of such units. This study involves assessing the condition of the turbine generator unit by extracting the feature information of its vibration signals. Based on previous research, we present an enhanced Hilbert–Huang transform (HHT) method with an energy-correlation fluctuation criterion to extract feature information and effectively verify the method with simulated signals. An inspection application based on the signal from a vortex strip in the draft tube of a prototype turbine under suboptimal operating conditions indicates that this method is more effective than the traditional one, with a better component identification capability and better suited to the analysis of the complex and dynamic feature information of hydro turbines. Highlights: Intense vibration in hydraulic turbine generator unit draft tubes leads to a run-out of the shafting of the unit. It assessed the condition of the unit by extracting information concerning its vibration signal features. An enhanced Hilbert Huang Transform (HHT) method with an energy-correlation fluctuation criterion was used.